Identifikasi Sifat dan Distribusi Sel Endokrin Ghrelin di Lambung Tikus (Rattus norvegicus): Studi Immunohis-Tokimia pada Kondisi Obesitas - Teguh Budipitojo; Hevi Wihadmadyatami; Ganies Riza Aristya (Universitas Gadjah Mada, 2016)
Obesity is one of major nutritional problems in the world. Obesity is very dangerous, especially when concentrated in the abdomen, because it is closely linked to various diseases such as diabetes, hypertension, heart disease, which can to causing death. This study aims to identify the nature and distribution of ghrelin on gastric endocrine cells in the obese rat (Rattus norvegicus) by using immunohistochemical techniques. The results will strengthen the understanding of the role and function of ghrelin as an alternative therapeutic target on obesity. The research used gastric tissues of ten obese and control rats which were stained with avidin-biotin-peroxidase complex method of immunohistochemistry. The results showed the existence of two types of ghrelin-producing cells (open and closed types) on the gastric mucosa of control rats, and only one type of ghrelin producing cells (open type) in obese rats. The intensity of ghrelin immunoreactive positive cells was detected weak in obese rats, but very strong in control rats. Ghrelin endocrine cells mainly distributed in the basal part of the gastric mucosa of the fundus parts, with a very small number in obese rats, but highly abundant in control rats. This study confirmed the decrease of the ghrelin synthesis and secretion in obese rat (Rattus norvegicus) at the cellular level. The decrease of ghrelin synthesis is characterized by a reduction on the number of ghrelin producing cells, the disappearance of the close type of ghrelin producing cells, and the low activity of protein synthesis in the ghrelin producing cells. Ghrelin endocrine cells distributed mainly in the basal part of the gastric mucosa, especially in the fundus parts.